Catalytic cracking catalyst as well as preparation method and application thereof
By rationally preparing molecular sieve, binder and clay in the catalyst and optimizing the mesoporous structure, the problems of poor catalytic activity and poor hydrothermal stability in the catalytic cracking reaction of naphtha are solved, and high conversion rate and low Effects of carbon olefin yield.
Patent Information
- Application Number
- CN202310849323.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-07-11
AI Technical Summary
The existing catalytic cracking catalysts have problems such as poor catalytic activity, poor hydrothermal stability, high cost and narrow mesoporous distribution in naphtha catalytic cracking reaction, resulting in low conversion and low carbon olefin yields.
A catalyst is used, including molecular sieve, binder and clay. The molecular sieve mass content is 60-85%, the clay mass content is 5-20%, the binder mass content is 10-35%, and the mesoporous pore size is 3-50nm , the mesoporous volume with a pore size of 6-10nm accounts for 8-30% of the total mesoporous volume, and the mesoporous volume with a pore size of 30-35nm accounts for 10-30%. It is prepared by beating, spray drying and calcining, combined with 27Al MAS NMR characterization ensures that the chemical displacement ratio of the molecular sieve is within the appropriate range.
The catalytic performance of the catalyst is improved, the mesoporous distribution is enhanced, the conversion rate and low carbon olefin yield of naphtha catalytic cracking reaction are improved, and the hydrothermal stability and mechanical strength of the catalyst are ensured.
Smart Images

Figure CN119303619A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalytic cracking catalyst preparation, and in particular to a catalytic cracking catalyst and a preparation method and application thereof. Background Art
[0002] At present, the main method for producing ethylene and propylene is steam thermal cracking. The most commonly used raw material is naphtha. However, steam thermal cracking of naphtha has the disadvantages of high reaction temperature, harsh process conditions, release of large amounts of CO2, and large losses. Catalytic cracking developed in recent years is a process for producing low-carbon olefins using petroleum hydrocarbons as raw materials, and there are many literature reports on catalysts related to it.
[0003] CN114425417A discloses a naphtha catalytic cracking catalyst and its preparation method and application. The catalyst contains 50-85% by weight of a carrier and 15-50% by weight of a core-shell molecular sieve. However, the preparation method of the core-shell molecular sieve is relatively complicated.
[0004] CN1413244A discloses a method of combining a modified mesoporous phosphate material as a catalyst with a primary catalytic cracking material to catalytically crack sulfur-containing hydrocarbon raw materials to prepare a small molecule hydrocarbon mixture, but the catalyst has poor hydrothermal stability, and the conversion rate of the raw material and the product yield are both low.
[0005] CN1274342A discloses a molecular sieve with a high silicon-aluminum ratio and a pore size between 0.5 and 0.65 nanometers as a catalyst, and uses light hydrocarbons containing olefins as raw materials to prepare ethylene and propylene, but the yield of ethylene and propylene is relatively low.
[0006] CN105582999B discloses a catalyst for producing propylene by catalytic cracking of naphtha and a preparation method thereof, wherein the catalyst is based on the total weight of the catalyst, and the catalyst contains 50-95% by weight of a molecular sieve and 5-50% by weight of a matrix; the molecular sieve contains a first molecular sieve and a second molecular sieve, wherein the first molecular sieve is a molecular sieve having a two-dimensional elliptical channel structure of a ten-membered ring, and the second molecular sieve is a molecular sieve having a twelve-membered ring channel structure. The diene yield is high, but multiple molecular sieves are required as active centers, and the cost price is relatively high. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems existing in the prior art and provide a catalytic cracking catalyst and its preparation and application. The catalyst has excellent catalytic performance and is applied to catalytic cracking reactions, especially to naphtha catalytic cracking reactions, with high conversion rate and light olefin yield.
[0008] In order to achieve the above object, the present invention provides a catalytic cracking catalyst, which comprises a molecular sieve, a binder and clay; based on the total mass of the catalyst, the mass content of the molecular sieve is 60-85%, the mass content of the clay is 5-20%, and the mass content of the binder is 10-35%;
[0009] The mesopore diameter of the catalyst is 3-50 nm;
[0010] In the catalyst, the volume of mesopores with a pore size of 6-10 nm accounts for 8-30% of the total mesopore volume;
[0011] In the catalyst, the volume of mesopores with a pore size of 30-35 nm accounts for 10-30% of the total mesopore volume. The second aspect of the present invention provides a method for preparing a catalytic cracking catalyst, the method comprising:
[0012] (1) slurrying the molecular sieve, the second suspension containing clay, and the first binder precursor to obtain a first slurry;
[0013] (2) beating the first slurry with at least a portion of the second binder precursor to obtain a second slurry having a viscosity of no more than 0.1 Pa·s;
[0014] (3) beating the second slurry and the third binder precursor to obtain a third slurry having a viscosity of not less than 1 Pa·s;
[0015] (4) aging the third slurry and the amphiphilic block polymer to obtain a fourth slurry;
[0016] (5) spray drying the fourth slurry and then calcining it;
[0017] through 27 According to Al MAS NMR characterization, the ratio of the peak area of the resonance signal of the molecular sieve at a chemical shift of 45±1 ppm to the peak area of the resonance signal at a chemical shift of 53±1 ppm is not greater than 1.5.
[0018] The third aspect of the present invention provides a use of the catalytic cracking catalyst described in the first aspect or the catalytic cracking catalyst prepared by the method described in the second aspect in a catalytic cracking reaction.
[0019] Through the above technical solution, the beneficial effects of the present invention include:
[0020] The catalyst of the present invention has a high molecular sieve content and a wide mesopore size distribution, so that the catalyst of the present invention has excellent catalytic performance. The catalyst of the present invention is applied to catalytic cracking reaction, especially to naphtha catalytic cracking reaction, and has a high conversion rate and low-carbon olefin yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a mesopore distribution diagram of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2;
[0022] Figure 2 This is the macropore distribution diagram of the catalyst prepared in Example 1. DETAILED DESCRIPTION
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] The dry basis of the present invention refers to that obtained by calcining at 550° C. for 2 hours.
[0025] In one aspect, the present invention provides a catalytic cracking catalyst, which comprises a molecular sieve, a binder and clay; based on the total mass of the catalyst, the mass content of the molecular sieve is 60-85%, the mass content of the clay is 5-20%, and the mass content of the binder is 10-35%;
[0026] The mesopore diameter of the catalyst is 3-50 nm;
[0027] In the catalyst, the volume of mesopores with a pore size of 6-10 nm accounts for 8-30% of the total mesopore volume;
[0028] In the catalyst, the volume of mesopores with a pore diameter of 30-35 nm accounts for 10-30% of the total mesopore volume.
[0029] The mesopore distribution of the prior art catalytic cracking catalyst is relatively narrow, generally at the level of 6-10nm, and has the defect that the active center of the catalyst is difficult to expose, resulting in poor catalytic activity. However, the mesopore distribution of the catalyst of the present invention is relatively wide, which is conducive to the exposure of the active center of the molecular sieve and the smooth flow of the catalyst pores, thereby improving the catalytic activity of the catalyst.
[0030] In order to further improve the catalytic performance of the catalyst, preferably, based on the total mass of the catalyst, the mass content of the molecular sieve is 60-70%, the mass content of the clay is 5-20%, and the mass content of the binder is 16-35%.
[0031] The content of each component of the catalyst of the present invention is calculated by feeding ratio.
[0032] According to the present invention, preferably, the mesopore diameter of the catalyst is 6-50 nm.
[0033] The mesopore diameter of the catalyst of the present invention is measured by the N2 adsorption BET method.
[0034] The catalyst of the present invention has abundant mesopores, which is beneficial to improving the catalytic activity of the catalyst. According to the present invention, preferably, the volume of the mesopores of the catalyst accounts for 40-70% of the total pore volume of the catalyst, preferably 45-60%.
[0035] The pore volume distribution of the catalyst of the present invention is measured by N2 adsorption BET method and mercury intrusion method.
[0036] According to the present invention, preferably, the macropore diameter of the catalyst is 90-435 nm.
[0037] The pore diameter of the catalyst macropores of the present invention is measured by mercury intrusion porosimetry.
[0038] According to the present invention, preferably, the porosity of the catalyst is not greater than 66%, preferably 50-65%. This preferred embodiment ensures both the proximity of the active center of the molecular sieve and the mechanical strength of the catalyst.
[0039] The porosity of the catalyst of the present invention is measured by mercury intrusion porosimetry.
[0040] According to the present invention, preferably, the average crystal size of the molecular sieve is 100-500 nm, preferably 200-300 nm. This preferred embodiment is beneficial to increase the contact probability between the reactants and the catalytic active sites, thereby improving the reaction activity of the catalyst.
[0041] In the present invention, when the crystal grains are spherical, the crystal grain size refers to the crystal grain diameter; when the crystal grains are quasi-spherical, the crystal grain size refers to the diameter of the largest circumscribed circle thereof.
[0042] The average grain size of the present invention is measured by transmission electron microscopy, specifically, 10 molecular sieve grains are randomly selected, their grain sizes are measured, and then the average value is obtained.
[0043] According to the present invention, preferably, the SiO2 / Al2O3 molar ratio of the molecular sieve is 25-200, preferably 25- 100. This preferred embodiment is conducive to improving the catalytic activity of the catalyst.
[0044] According to the present invention, preferably, 27 According to Al MAS NMR characterization, the ratio of the characteristic peak area of the molecular sieve at a chemical shift of 45±1 ppm to the characteristic peak area at a chemical shift of 53±1 ppm is not greater than 1.5, preferably 0.35-1.5. The preferred embodiment enables the prepared catalyst to have good hydrothermal stability.
[0045] The present invention has a wide range of selection for the type of the molecular sieve, as long as it meets the characteristics of the above molecular sieves. Preferably, the molecular sieve is at least one of ZSM-5 molecular sieve, IM-5 molecular sieve and ZSM-22 molecular sieve.
[0046] The present invention has a wide range of clay types, which can be selected from conventional choices in the art. Preferably, the clay is selected from at least one of kaolin, halloysite, reuterite and montmorillonite.
[0047] According to the present invention, preferably, the adhesive includes a first adhesive, a second adhesive and a third adhesive.
[0048] According to the present invention, preferably, the first binder is obtained by calcining at least one of pseudo-boehmite, hydrated alumina with a diaspore structure, hydrated alumina with a gibbsite structure, hydrated alumina with a bayerite structure, γ-alumina, η-alumina, θ-alumina and x-alumina.
[0049] The present invention has no particular limitation on the source of the first binder, which can be obtained from commercial sources or prepared in a conventional manner.
[0050] According to the present invention, preferably, the second binder is obtained by calcining aluminum sol.
[0051] According to the present invention, preferably, the third binder is obtained by calcining phosphate aluminum glue.
[0052] The present invention has no particular limitation on the calcination conditions. For example, the calcination conditions may be the calcination conditions in the following preparation method.
[0053] According to the present invention, preferably, the mass ratio of the second binder to the first binder is 1-4, preferably 1.7-4.
[0054] According to the present invention, preferably, the mass ratio of the second binder to the third binder is 0.3-1, preferably 0.3-0.8.
[0055] The present invention adopts three kinds of binders in a specific ratio to form a catalyst with a porous structure.
[0056] According to the present invention, preferably, the aluminum sol has an aluminum-chlorine ratio of no more than 1.4, preferably 1.2-1.3. This preferred embodiment can minimize the degree of damage to the molecular sieve framework while ensuring the bonding performance of the binder, which is beneficial to improving the reaction activity of the catalyst.
[0057] The aluminum-chlorine ratio of the aluminum sol described in the present invention is measured by X-ray fluorescence spectrometry.
[0058] The present invention has no particular limitation on the source of the aluminum sol, which can be obtained from commercial sources or prepared in-house according to conventional methods.
[0059] According to the present invention, preferably, the phosphate aluminum gel has a network structure.
[0060] The structure of the phosphoaluminum gel of the present invention is measured by a transmission electron microscope.
[0061] In the prior art, phosphate aluminum gel generally has a dispersed spherical nanoparticle structure, which has the defects of poor bonding performance and unstable structure. However, the inventors found in the research process that phosphate aluminum gel with a mesh structure has both excellent bonding performance and a stable skeleton structure, which is conducive to improving the mechanical strength of the catalyst.
[0062] According to the present invention, preferably, the mass ratio of Al2O3 to P2O5 in the phosphate aluminum colloid is 0.25-0.35. This preferred embodiment ensures that the phosphate aluminum colloid has a rich network structure.
[0063] The mass ratio of Al2O3 to P2O5 in the phosphate aluminum gel of the present invention is measured by X-ray fluorescence spectrometry.
[0064] According to the present invention, preferably, the pH of the phosphate aluminum gel is 1-3, preferably 2-3. This preferred embodiment can ensure the structure and stability of the phosphate aluminum gel binder, while ensuring the stability of the molecular sieve structure, which is further beneficial to improving the reaction activity and mechanical strength of the catalyst.
[0065] The present invention has no particular limitation on the preparation method of the above-mentioned phosphate aluminum gel, as long as the phosphate aluminum gel with the above-mentioned composition and characteristics can be prepared. In order to further improve the catalytic performance of the catalyst, the present invention also provides a preparation method of the above-mentioned phosphate aluminum gel.
[0066] According to the present invention, preferably, the method for preparing the phosphate aluminum gel comprises: mixing an acid-soluble aluminum precursor with water for slurrying, and then adding a phosphoric acid solution at 45-55° C. to react to obtain the phosphate aluminum gel.
[0067] According to the present invention, preferably, the reaction conditions include: temperature of 75-85° C., and time of 1-2 h.
[0068] In the preparation method of the phosphate aluminum gel described in the present invention, by controlling the temperature of adding phosphoric acid, and preferably further controlling the reaction conditions, the composition and characteristics of the prepared phosphate aluminum gel meet the above requirements, which is beneficial for the prepared catalyst to have excellent catalytic performance and high mechanical strength.
[0069] The present invention has no particular limitation on the amount of the acid-soluble aluminum precursor and the phosphoric acid solution, as long as the mass ratio of Al2O3 to P2O5 in the obtained phosphate aluminum gel is 0.25-0.35.
[0070] The present invention has no particular limitation on the amount of water used, as long as the pH of the phosphate aluminum gel is within the above range.
[0071] The present invention has a wide range of choices for the acid-soluble aluminum precursor, which can be a conventional choice in the art. Preferably, the acid-soluble aluminum precursor is selected from at least one of pseudo-boehmite, aluminum oxide, aluminum hydroxide, aluminum isopropoxide and aluminum isobutoxide, preferably pseudo-boehmite.
[0072] A second aspect of the present invention provides a method for preparing a catalytic cracking catalyst, the method comprising:
[0073] (1) slurrying the molecular sieve, the second suspension containing clay, and the first binder precursor to obtain a first slurry;
[0074] (2) slurrying the first slurry and at least a portion of the second binder precursor to obtain a second slurry having a viscosity of no more than 0.1 Pa·s;
[0075] (3) beating the second slurry and the third binder precursor to obtain a third slurry having a viscosity of not less than 1 Pa·s;
[0076] (4) aging the third slurry and the amphiphilic block polymer to obtain a fourth slurry;
[0077] (5) spray drying the fourth slurry and then calcining it;
[0078] through 27 According to Al MAS NMR characterization, the ratio of the peak area of the resonance signal of the molecular sieve at a chemical shift of 45±1 ppm to the peak area of the resonance signal at a chemical shift of 53±1 ppm is not greater than 1.5.
[0079] In the prior art, the molecular sieve content of the spray-formed catalyst is relatively low, generally not higher than 40wt%, which is mainly due to the need to ensure that the mechanical strength of the catalyst meets the requirements of the catalytic cracking reaction. When the molecular sieve content is too high, spray forming is more difficult, and the catalyst wear index is too high (higher than 10% / h), resulting in poor catalyst stability. The catalyst obtained by the method provided by the present invention overcomes the above-mentioned defects, so that the mechanical strength of the prepared catalyst meets the requirements of the catalytic cracking reaction, and it has a high molecular sieve content and a wider mesopore distribution. It is applied to catalytic cracking reactions, especially to naphtha catalytic cracking reactions, and has a higher reactant conversion rate and a higher ethylene propylene yield.
[0080] In the present invention, the viscosity of the second slurry is not greater than 0.1 Pa·s, preferably 0.05-0.1 Pa·s. This preferred embodiment is advantageous for obtaining a uniform catalyst (ie, each component is evenly distributed).
[0081] In the present invention, the viscosity of the third slurry is not less than 1 Pa·s, preferably 1-2 Pa·s. This preferred embodiment is beneficial to improving the mechanical strength of the catalyst.
[0082] The viscosity of the present invention is measured by a viscometer.
[0083] The present invention has no particular limitation on the specific conditions of pulping (mentioned above and below) in the preparation method, and it can be carried out by conventional methods in the art, which is not limited here.
[0084] According to the present invention, preferably, the amounts of the clay, molecular sieve and binder precursor are such that in the prepared catalyst, based on the total mass of the catalyst, the mass content of the clay is 5-20%, the mass content of the molecular sieve is 60-85%, and the mass content of the binder is 10-35%, and the binder is the sum of the first binder, the second binder and the third binder.
[0085] Further preferably, the amounts of the clay, molecular sieve and binder precursors are such that in the prepared catalyst, based on the total mass of the catalyst, the mass content of the clay is 5-20%, the mass content of the molecular sieve is 60-70%, and the mass content of the binder is 16-35%, and the binder is the sum of the first binder, the second binder and the third binder.
[0086] According to the present invention, preferably, the dry weight ratio of the second binder precursor to the first binder precursor is 1-4, preferably 1.7-4.
[0087] According to the present invention, preferably, the dry basis mass ratio of the second binder precursor to the third binder precursor is 0.3-1, preferably 0.3-0.8.
[0088] According to the present invention, preferably, the average crystal size of the molecular sieve is 100-500 nm, preferably 200-300 nm.
[0089] According to the present invention, preferably, the SiO2 / Al2O3 molar ratio of the molecular sieve is 25-200, preferably 25-100.
[0090] According to the present invention, preferably, 27According to Al MAS NMR characterization, the ratio of the characteristic peak area of the molecular sieve at a chemical shift of 45±1 ppm to the characteristic peak area at a chemical shift of 53±1 ppm is 0.35-1.5.
[0091] The present invention has a wide range of selection for the type of the molecular sieve, as long as it meets the characteristics of the above molecular sieves. Preferably, the molecular sieve is at least one of ZSM-5 molecular sieve, IM-5 molecular sieve and ZSM-22 molecular sieve.
[0092] The present invention has a wide range of clay types, which can be selected from conventional choices in the art. Preferably, the clay is selected from at least one of kaolin, halloysite, reuterite and montmorillonite.
[0093] According to the present invention, preferably, the first binder precursor is selected from at least one of pseudo-boehmite, hydrated alumina with a diaspore structure, hydrated alumina with a gibbsite structure, hydrated alumina with a bayerite structure, γ-alumina, η-alumina, θ-alumina and x-alumina.
[0094] According to the present invention, preferably, the second binder precursor is aluminum sol.
[0095] According to the present invention, preferably, the aluminum sol has an aluminum-chlorine ratio of no higher than 1.4, preferably 1.2-1.3.
[0096] The present invention has no particular limitation on the source of the aluminum sol, which can be obtained from commercial sources or prepared in-house according to conventional methods.
[0097] According to the present invention, preferably, the third binder precursor is phosphate aluminum gel.
[0098] According to the present invention, preferably, the phosphate aluminum gel has a network structure.
[0099] According to the present invention, preferably, the mass ratio of Al2O3 to P2O5 in the phosphate aluminum gel is 0.25-0.35.
[0100] According to the present invention, preferably, the pH of the phosphate aluminum gel is 1-3, preferably 2-3.
[0101] According to the present invention, preferably, the method for preparing the phosphate aluminum gel comprises: mixing an acid-soluble aluminum precursor with water for slurrying, and then adding a phosphoric acid solution at 45-55° C. to react to obtain the phosphate aluminum gel.
[0102] According to the present invention, preferably, the reaction conditions include: temperature of 75-85° C., and time of 1-2 h.
[0103] According to the present invention, preferably, the acid-soluble aluminum precursor is selected from at least one of pseudo-boehmite, aluminum oxide, aluminum hydroxide, aluminum isopropoxide and aluminum isobutoxide, preferably pseudo-boehmite.
[0104] The present invention has no particular limitation on the order of adding the molecular sieve, the second suspension containing clay and the first binder precursor in step (1), and they can be added separately or together. The embodiment of the present invention adopts the method of adding together as an example.
[0105] Preferably, the molecular sieve is provided in the form of a first suspension.
[0106] The present invention has a wide range of choices for the type of the first liquid medium in the first suspension, which can be a conventional choice in the art. Preferably, the first liquid medium is water and / or an organic solvent, preferably water.
[0107] The present invention has no particular limitation on the amount of the first liquid medium in the first suspension, as long as the solid content in the first suspension is within 30-40 wt %.
[0108] According to the present invention, preferably, the second suspension is obtained by slurrying clay, the second liquid medium and optionally the remaining part of the second binder precursor. With this preferred embodiment, the clay has good fluidity while ensuring that the solid content of the second suspension is maintained at a high level.
[0109] According to the present invention, preferably, the dry basis mass of the remaining second binder precursor is 5-15% of the dry basis mass of the clay.
[0110] The present invention has a wide range of choices for the type of the second liquid medium in the second suspension, and can be a conventional choice in the art.
[0111] According to a preferred embodiment of the present invention, the second liquid medium is of the same type as the first liquid medium.
[0112] The present invention has no particular limitation on the amount of the second liquid medium in the second suspension, as long as the solid content in the second suspension is within the range of 28-38 wt %.
[0113] Preferably, the first binder precursor is provided in the form of a third suspension.
[0114] Preferably, the preparation method of the third suspension comprises: firstly slurrying the first binder precursor and the third liquid medium, and then mixing them with an acid.
[0115] Preferably, the acid is an inorganic acid, preferably hydrochloric acid and / or nitric acid. The above substances are conventionally selected in the art and can be obtained commercially.
[0116] Preferably, the weight ratio of the acid to the first binder precursor on a dry basis is 0.1-1:1.
[0117] The present invention has a wide range of choices for the type of the third liquid medium in the third suspension, which can be a conventional choice in the art.
[0118] According to a preferred embodiment of the present invention, the third liquid medium is of the same type as the first liquid medium.
[0119] The present invention has no particular limitation on the amount of the third liquid medium in the third suspension, as long as the solid content in the third suspension is within the range of 10-25 wt %.
[0120] According to the present invention, preferably, the aging conditions in step (4) include: a temperature of 50-85°C, preferably 60-80°C; and a time of 0.5-4h, preferably 1-2h.
[0121] The present invention ages the third slurry and the amphiphilic block polymer under specific conditions, which is more conducive to improving the reaction activity of the catalyst of the present invention. When the aging temperature is lower than the range of the present invention, it is difficult to obtain a relatively rich mesoporous structure; when the aging temperature is higher than the range of the present invention, the binder in the catalyst slurry is easy to coagulate, which is not conducive to the subsequent spray drying.
[0122] It should be noted that if the aging time in the present invention is too long, the binder is easy to coagulate, which is not conducive to the subsequent spray drying.
[0123] According to the present invention, preferably, the mass amount of the amphiphilic block polymer is 5-30%, preferably 10-20%, of the third slurry on a dry basis.
[0124] Adding the amphiphilic block polymer in step (4) of the present invention is beneficial to obtaining the catalyst having the pore structure according to the first aspect of the present invention.
[0125] The amphiphilic block polymer described in the present invention refers to a block compound containing both a hydrophilic segment and a lipophilic segment, which is a well-known definition in the art.
[0126] The block polymer of the present invention can be selected from a wide range of types, and can be various amphiphilic block polymers commonly used in the art. In order to improve the catalytic performance of the catalyst, it is further preferred that the block polymer is selected from at least one of polyethylene glycol-b-polypropylene glycol, polystyrene-b-polyacrylic acid and polystyrene-b-polyethylene glycol.
[0127] The present invention has no particular limitation on the source of the amphiphilic block polymer, which can be prepared by conventional methods in the art or purchased commercially.
[0128] The present invention has no particular limitation on the specific conditions of the spray drying in step (5), which can be carried out according to conventional methods in the art, and the present invention does not impose any limitation thereon.
[0129] The present invention has no particular limitation on the conditions for the calcination in step (5), and the calcination may be carried out according to conventional methods in the art. Preferably, the calcination conditions in step (5) include: a temperature of 400-800° C. and a time of 1-12 h. The calcination is generally carried out in an air atmosphere, which may include a flowing atmosphere or a static atmosphere.
[0130] In the present invention, the "first", "second" and "third" do not limit the substances and operations, but are only used to distinguish the substances introduced in different steps and the operations performed in different stages.
[0131] The third aspect of the present invention provides an application of the catalytic cracking catalyst described in the first aspect or the catalytic cracking catalyst prepared by the method described in the second aspect in a catalytic cracking reaction, preferably in a catalytic cracking reaction of naphtha.
[0132] The present invention has no particular limitation on the conditions of the catalytic cracking reaction, and the reaction can be carried out according to conventional methods in the art.
[0133] In order to better illustrate the stability of the catalyst of the present invention in the application of catalytic cracking reaction, it was hydrothermally aged before use.
[0134] The hydrothermal aging temperature of the catalytic cracking catalyst in the prior art is generally not more than 800°C, and the time is also relatively short, generally not more than 17 hours. The aging conditions of the hydrothermal aging described in the present invention are more stringent, and are used to better reflect the actual application degree of the industry. Preferably, the hydrothermal aging conditions include: a temperature of 820-850°C and a time of 20-72 hours.
[0135] Preferably, the hydrothermal aging is carried out under the condition of 100% water vapor.
[0136] The present invention will be described in detail below through examples.
[0137] In the following examples, the aluminum sol is a commercial product of Sinopec Catalyst Company Qilu Branch, with a solid content of 21.5% by weight;
[0138] Pseudo-boehmite is a commercial product from Shandong Aluminum Plant, with a solid content of 66.9 wt %;
[0139] ZSM-5 molecular sieve is a commercial product of Tianjin Nanhua Catalyst Co., Ltd., with a dry basis mass of 97.8% by weight;
[0140] ZSM-22 molecular sieve is a commercial product of Tianjin Nanhua Catalyst Co., Ltd., with a dry basis mass of 98.5% by weight;
[0141] Kaolin was a commercial product from Suzhou Kaolin Company, with a dry basis mass of 84.6 wt%;
[0142] Polyethylene glycol-b-polypropylene glycol is a commercial product of Sigma-Aldrich with brand number 438197;
[0143] Polystyrene-b-polyacrylic acid is a commercial product of Sigma-Aldrich with the brand number 776351;
[0144] Polystyrene-b-polyethylene glycol is a commercial product of Xi'an Qiyue Biotechnology Co., Ltd. with the brand number Q-0000920.
[0145] Preparation Examples 1-3 are used to illustrate the preparation of the phosphoaluminum gel described in the present invention.
[0146] Preparation Example 1
[0147] 0.55 kg of pseudo-boehmite and 1.45 kg of deionized water were weighed and slurried evenly, then heated to 50° C., 2.00 kg of phosphoric acid (concentration 85 wt%) was added, and heated to 80° C. for 90 min to prepare phosphoaluminum gel. The phosphoaluminum gel has a network structure, a mass ratio of Al2O3 to P2O5 of 0.3, and a pH of 2.
[0148] Preparation Example 2
[0149] 0.51 kg of pseudo-boehmite and 1.41 kg of deionized water were weighed and slurried evenly, then heated to 45° C., 2.00 kg of phosphoric acid (concentration 85 wt%) was added, and heated to 80° C. for 60 min to prepare phosphoaluminum colloid. The phosphoaluminum colloid has a network structure, a mass ratio of Al2O3 to P2O5 of 0.28, and a pH of 2.2.
[0150] Preparation Example 3
[0151] 0.64 kg of pseudo-boehmite and 1.45 kg of deionized water were weighed and slurried evenly, then heated to 55° C., and then 2.00 kg of phosphoric acid (concentration 85 wt%) was added, heated to 75° C., and reacted for 60 minutes to prepare phosphoaluminum gel. The phosphoaluminum gel has a network structure, a mass ratio of Al2O3 to P2O5 of 0.35, and a pH of 2.5.
[0152] Example 1
[0153] Weigh 6.65kg of ZSM-5 molecular sieve and slurry with deionized water to prepare a ZSM-5 molecular sieve suspension with a solid content of 33wt%. Weigh 1.18kg of kaolin, 0.47kg of aluminum sol and deionized water to slurry to prepare a kaolin suspension with a solid content of 38wt%. Weigh 0.45kg of pseudo-boehmite and slurry with deionized water to prepare a pseudo-boehmite suspension with a solid content of 17wt%. Then add hydrochloric acid (the weight ratio of the acid to the first binder precursor on a dry basis is 0.13) to prepare a pseudo-boehmite suspension with a solid content of 17wt%. Slurry the above kaolin suspension, pseudo-boehmite suspension and molecular sieve suspension for 15 minutes to obtain a first slurry. Add 2.33kg of aluminum sol to the first slurry and slurry for 5 minutes to obtain a second slurry. Add 4kg of phosphoaluminum colloid obtained in Preparation Example 1 to the second slurry and slurry for 5 minutes to obtain a third slurry. 200 mL of polyethylene glycol-b-polypropylene glycol aqueous solution was added to the third slurry, then heated to 60°C, aged for 1 hour, and cooled to room temperature to obtain a fourth slurry. The fourth slurry was spray dried and then calcined at 550°C for 2 hours to obtain a catalyst, which was recorded as A. Some conditions in the catalyst preparation process are shown in Table 1. The catalyst composition and characteristic parameters are shown in Table 2.
[0154] The mesopore distribution of the catalyst prepared in Example 1 is exemplified as follows: Figure 1 As shown, it can be seen that the catalyst has a wide mesopore distribution at 6-50nm.
[0155] The macropore distribution of the catalyst prepared in Example 1 is exemplified as follows: Figure 2 As shown, it can be seen that the catalyst has an obvious macropore distribution at 95-432nm.
[0156] Example 2
[0157] Weigh 12.26kg of ZSM-22 molecular sieve and slurry with deionized water to prepare a ZSM-22 molecular sieve suspension with a solid content of 36wt%. Weigh 3.54kg of kaolin, 1.40kg of aluminum sol and deionized water to slurry evenly to prepare a kaolin suspension with a solid content of 38wt%. Weigh 0.45kg of pseudo-boehmite and slurry with deionized water, then add hydrochloric acid (the weight ratio of the acid to the first binder precursor on a dry basis is 0.12) to prepare a pseudo-boehmite suspension with a solid content of 21wt%. Slurry the above-mentioned kaolin suspension, pseudo-boehmite suspension and molecular sieve suspension for 15 minutes to obtain a first slurry. Add 4.18kg of aluminum sol to the first slurry and slurry for 5 minutes to obtain a second slurry. Add 3.92kg of phosphoaluminum colloid obtained in Preparation Example 2 to the second slurry and slurry for 5 minutes to obtain a third slurry. 225 mL of polystyrene-b-polyacrylic acid aqueous solution was added to the third slurry, then heated to 60°C, aged for 1.5 hours, and cooled to room temperature to obtain a fourth slurry. The fourth slurry was spray dried and then calcined at 550°C for 2 hours to obtain a catalyst, which was recorded as B. Some conditions in the catalyst preparation process are shown in Table 1. The catalyst composition and characteristic parameters are shown in Table 2.
[0158] Example 3
[0159] Weigh 10.74kg of ZSM-5 molecular sieve and slurry with deionized water to prepare a ZSM-5 molecular sieve suspension with a solid content of 31wt%. Weigh 1.40kg of kaolin, 0.50kg of aluminum sol and deionized water to slurry to prepare a kaolin suspension with a solid content of 30wt%. Weigh 0.8kg of pseudo-boehmite and slurry with deionized water to prepare a pseudo-boehmite suspension with a solid content of 20wt%. Then add concentrated hydrochloric acid (the weight ratio of the acid to the first binder precursor on a dry basis is 0.1) to prepare a pseudo-boehmite suspension with a solid content of 20wt%. Slurry the above kaolin suspension, pseudo-boehmite suspension and molecular sieve suspension for 15 minutes to obtain a first slurry. Add 5.14kg of aluminum sol to the first slurry and slurry for 5 minutes to obtain a second slurry. Add 4.09kg of phosphoaluminum colloid obtained in Preparation Example 3 to the second slurry and slurry for 5 minutes to obtain a third slurry. 150 mL of polystyrene-b-polyethylene glycol aqueous solution was added to the third slurry, then heated to 75°C, aged for 1.5 hours, and cooled to room temperature to obtain a fourth slurry. The fourth slurry was spray dried and then calcined at 550°C for 2 hours to obtain a catalyst, which was recorded as C. Some conditions in the catalyst preparation process are shown in Table 1. The catalyst composition and characteristic parameters are shown in Table 2.
[0160] Comparative Example 1
[0161] Weigh 4.21kg of ZSM-5 molecular sieve and slurry with deionized water to prepare a ZSM-5 molecular sieve suspension with a solid content of 33wt%. Weigh 1.15kg of kaolin, 0.47kg of aluminum sol and deionized water to slurry to prepare a kaolin suspension with a solid content of 38wt%. Weigh 0.55kg of pseudo-boehmite and slurry with deionized water to prepare a pseudo-boehmite suspension with a solid content of 17wt%. Then add hydrochloric acid (the weight ratio of the acid to the first binder precursor on a dry basis is 0.13) to prepare a pseudo-boehmite suspension with a solid content of 17wt%. Slurry the above-mentioned kaolin suspension, pseudo-boehmite suspension and molecular sieve suspension for 15min to obtain a first slurry. Add 4.66kg of aluminum sol to the first slurry and slurry for 5min to obtain a second slurry. Spray dry the second slurry and then calcine at 550℃ for 2 hours to obtain a catalyst, which is recorded as D. Some conditions in the catalyst preparation process are shown in Table 1. The catalyst composition and characteristic parameters are shown in Table 2.
[0162] The mesopore distribution of catalyst D is as follows: Figure 1 As shown, it can be seen that there is no pore size distribution in the 6-50 nm mesopore.
[0163] Comparative Example 2
[0164] The method of Example 2 was followed, except that the polystyrene-b-polyacrylic acid aqueous solution was not added, and the third slurry was directly spray-dried and calcined to obtain a catalyst, which was recorded as E. Some conditions in the catalyst preparation process are shown in Table 1. The catalyst composition and characteristic parameters are shown in Table 2.
[0165] The mesopore distribution of catalyst E is as follows: Figure 1 As shown, it can be seen that there is no pore size distribution in the 6-50 nm mesopore.
[0166] Comparative Example 3
[0167] The method of Example 1 was followed, except that 2.33 kg of phosphoaluminum gel was added to the second slurry and 4 kg of aluminum sol was added to the third slurry to obtain a catalyst, which was recorded as F. Some conditions in the catalyst preparation process are shown in Table 1. The catalyst composition and characteristic parameters are shown in Table 2.
[0168] Table 1
[0169]
[0170] Note: The molar ratio of silicon to aluminum is the molar ratio of SiO2 / Al2O3
[0171] Table 2
[0172]
[0173] Note: X represents the proportion of mesopore volume with pore size of 6-10 nm to the total mesopore volume, %;
[0174] Y represents: the proportion of the volume of mesopores with pore diameter of 30-35nm to the total mesopore volume, %.
[0175] Test Example 1
[0176] Catalysts AF prepared in the examples and comparative examples were subjected to hydrothermal aging treatment at 820°C, 100% steam, for 20 hours, and then subjected to naphtha cracking reaction evaluation. The detailed conditions for micro-reaction evaluation are: catalyst loading 9.0g, feedstock oil is Yanshan Changding naphtha, the composition of which is shown in Table 3, catalyst-to-oil ratio (mass ratio of catalyst to naphtha) is 10, and reaction temperature is 600°C. The evaluation data of the reaction for 90s are shown in Table 4.
[0177] Table 3
[0178]
[0179] Note: C Num Refers to the number of carbons.
[0180] Table 4
[0181]
[0182]
[0183] It can be seen from the results in Table 4 that the application of the catalyst of the present invention in the catalytic cracking reaction of naphtha has a higher reactant conversion rate and a higher ethylene and propylene yield. At the same time, it can be shown from Table 4 that the catalyst of the present invention has good hydrothermal stability.
[0184] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalytic cracking catalyst, characterized in that: The catalyst comprises molecular sieve, binder and clay; based on the total mass of the catalyst, the mass content of the molecular sieve is 60-85%, the mass content of the clay is 5-20%, and the mass content of the binder is 10-35%; The mesopore diameter of the catalyst is 3-50 nm; In the catalyst, the volume of mesopores with a pore size of 6-10 nm accounts for 8-30% of the total mesopore volume; In the catalyst, the volume of mesopores with a pore diameter of 30-35 nm accounts for 10-30% of the total mesopore volume.
2. The catalyst according to claim 1, wherein Based on the total mass of the catalyst, the mass content of the molecular sieve is 60-70%, the mass content of the clay is 5-20%, and the mass content of the binder is 16-35%; Preferably, the mesopore diameter of the catalyst is 6-50 nm; Preferably, the mesopore volume of the catalyst accounts for 40-70%, preferably 45-60% of the total pore volume of the catalyst; Preferably, the macropore diameter of the catalyst is 90-435 nm; Preferably, the porosity of the catalyst is no greater than 66%, preferably 50-65%.
3. The catalyst according to claim 1, wherein The average crystal size of the molecular sieve is 100-500nm, preferably 200-300nm; Preferably, the SiO2 / Al2O3 molar ratio of the molecular sieve is 25-200, preferably 25-100; Preferably, 27 Al MAS NMR characterization, the ratio of the characteristic peak area of the molecular sieve at a chemical shift of 45±1ppm to the characteristic peak area at a chemical shift of 53±1ppm is not greater than 1.5, preferably 0.35-1.5; Preferably, the molecular sieve is at least one selected from ZSM-5 molecular sieve, IM-5 molecular sieve and ZSM-22 molecular sieve.
4. The catalyst according to any one of claims 1 to 3, wherein The adhesive comprises a first adhesive, a second adhesive and a third adhesive; Preferably, the first binder is obtained by calcining at least one of pseudo-boehmite, hydrated alumina with a diaspore structure, hydrated alumina with a gibbsite structure, hydrated alumina with a Bayerite structure, γ-alumina, η-alumina, θ-alumina and x-alumina; Preferably, the second binder is obtained by calcining aluminum sol; Preferably, the third binder is obtained by calcining phosphate aluminum glue; Preferably, the mass ratio of the second binder to the first binder is 1-4, preferably 1.7-4; Preferably, the mass ratio of the second binder to the third binder is 0.3-1, preferably 0.3-0.
8.
5. The catalyst according to claim 4, wherein The aluminum sol has an aluminum-chlorine ratio of no more than 1.4, preferably 1.2-1.3; Preferably, the phosphate aluminum gel has a mesh structure; Preferably, the mass ratio of Al2O3 to P2O5 in the phosphate aluminum gel is 0.25-0.35; Preferably, the pH of the phosphate aluminum gel is 1-3, preferably 2-3.
6. The catalyst according to claim 5, wherein The preparation method of the phosphate aluminum gel comprises: mixing an acid-soluble aluminum precursor with water for slurrying, and then adding a phosphoric acid solution at 45-55° C. to react to obtain the phosphate aluminum gel; Preferably, the reaction conditions include: temperature of 75-85°C, time of 1-2h; Preferably, the acid-soluble aluminum precursor is selected from at least one of pseudo-boehmite, aluminum oxide, aluminum hydroxide, aluminum isopropoxide and aluminum isobutoxide.
7. A method for preparing a catalytic cracking catalyst, the method comprising: (1) slurrying the molecular sieve, the second suspension containing clay, and the first binder precursor to obtain a first slurry; (2) slurrying the first slurry and at least a portion of the second binder precursor to obtain a second slurry having a viscosity of no more than 0.1 Pa·s; (3) beating the second slurry and the third binder precursor to obtain a third slurry having a viscosity of not less than 1 Pa·s; (4) aging the third slurry and the amphiphilic block polymer to obtain a fourth slurry; (5) spray drying the fourth slurry and then calcining it; through 27 According to Al MAS NMR characterization, the ratio of the peak area of the resonance signal of the molecular sieve at a chemical shift of 45±1 ppm to the peak area of the resonance signal at a chemical shift of 53±1 ppm is not greater than 1.
5.
8. The method according to claim 7, wherein: The clay, molecular sieve and binder precursor are used in such amounts that, based on the total mass of the catalyst, the mass content of the clay is 5-20%, the mass content of the molecular sieve is 60-85%, and the mass content of the binder is 10-35%, wherein the binder is the sum of the first binder, the second binder and the third binder; Preferably, the clay, molecular sieve and binder precursor are used in such amounts that, based on the total mass of the catalyst, the mass content of the clay is 5-20%, the mass content of the molecular sieve is 60-70%, and the mass content of the binder is 16-35%, wherein the binder is the sum of the first binder, the second binder and the third binder; Preferably, the dry basis mass ratio of the second binder precursor to the first binder precursor is 1-4, preferably 1.7-4; Preferably, the dry basis mass ratio of the second binder precursor to the third binder precursor is 0.3-1, preferably 0.3-0.
8.
9. The method according to claim 7, wherein: The average crystal size of the molecular sieve is 100-500nm, preferably 200-300nm; Preferably, the SiO2 / Al2O3 molar ratio of the molecular sieve is 25-200, preferably 25-100; Preferably, 27 Al MAS NMR characterization shows that the ratio of the peak area of the resonance signal of the molecular sieve at a chemical shift of 45±1ppm to the peak area of the resonance signal at a chemical shift of 53±1ppm is 0.35-1.5; Preferably, the molecular sieve is at least one selected from ZSM-5 molecular sieve, IM-5 molecular sieve and ZSM-22 molecular sieve.
10. The method according to any one of claims 7 to 9, wherein: The first binder precursor is selected from at least one of pseudo-boehmite, hydrated alumina with a diaspore structure, hydrated alumina with a gibbsite structure, hydrated alumina with a Bayerite structure, γ-alumina, η-alumina, θ-alumina and x-alumina; Preferably, the second binder precursor is aluminum sol; Preferably, the aluminum sol has an aluminum-chlorine ratio of no higher than 1.4, preferably 1.2-1.3; Preferably, the third binder precursor is phosphate aluminum glue; Preferably, the phosphate aluminum gel has a mesh structure; Preferably, the mass ratio of Al2O3 to P2O5 in the phosphate aluminum gel is 0.25-0.35; Preferably, the pH of the phosphate aluminum gel is 1-3, preferably 2-3.
11. The method according to claim 10, wherein: The preparation method of the phosphate aluminum gel comprises: mixing an acid-soluble aluminum precursor with water for slurrying, and then adding a phosphoric acid solution at 45-55° C. to react to obtain the phosphate aluminum gel; Preferably, the reaction conditions include: temperature of 75-85°C, time of 1-2h; Preferably, the acid-soluble aluminum precursor is selected from at least one of pseudo-boehmite, aluminum oxide, aluminum hydroxide, aluminum isopropoxide and aluminum isobutoxide.
12. The method according to any one of claims 7 to 11, wherein: The aging conditions in step (4) include: a temperature of 50-85° C., preferably 60-80° C.; a time of 0.5-4 h, preferably 1-2 h; Preferably, the mass amount of the amphiphilic block polymer is 5-30% of the dry mass of the third slurry, preferably 10-20%; Preferably, the amphiphilic block polymer is selected from at least one of polyethylene glycol-b-polypropylene glycol, polystyrene-b-polyacrylic acid and polystyrene-b-polyethylene glycol.
13. Use of the catalytic cracking catalyst according to any one of claims 1 to 6 or the catalytic cracking catalyst obtained by the method according to any one of claims 7 to 12 in a catalytic cracking reaction, preferably in a catalytic cracking reaction of naphtha.
Citation Information
Patent Citations
Catalyst for producing propylene by catalytic cracking of naphtha, preparation method thereof, and method for producing propylene by catalytic cracking of naphtha
CN105582999B
Process for producing ethylene and propylene
CN1274342A
Catalytic cracking process using modified mesoporous aluminophosphate material
CN1413244A
Preparation method of mesoporous aluminum oxide / clay composite material
CN108097227A
Preparation method of catalytic cracking catalyst containing mesoporous aluminum oxide / clay composite material
CN108097285A
Cited By
Heat storage type catalyst as well as preparation and application thereof
CN119972156A